Agrobacterium tumefaciens ferritins play an important role in full virulence through regulating iron homeostasis and oxidative stress survival. (17th July 2020) - Yang, Jing; Pan, Xiaoyue; Xu, Yujuan; Li, Yuan; Xu, Nan; Huang, Zhiwei; Ye, Jingyang; Gao, Dawei; Guo, Minliang
Abstract: Ferritins are a large family of iron storage proteins, which are used by bacteria and other organisms to avoid iron toxicity and as a safe iron source in the cytosol. Agrobacterium tumefaciens, a phytopathogen, has two ferritin‐encoding genes: atu2771 and atu2477 . Atu2771 is annotated as a Bfr‐encoding gene (Bacterioferritin, Bfr) and atu2477 as a Dps‐encoding gene (D NA binding p rotein from s tarved cells, Dps). Three deletion mutants (Δ bfr, Δ dps, and bfr ‐ dps double‐deletion mutant ΔbdF) of these two ferritin‐encoding genes were constructed to investigate the effects of ferritin deficiency on the iron homeostasis, oxidative stress resistance, and pathogenicity of A. tumefaciens . Deficiency of two ferritins affects the growth of A. tumefaciens under iron starvation and excess. When supplied with moderate iron, the growth of A. tumefaciens is not affected by the deficiency of ferritin. Deficiency of ferritin significantly reduces iron accumulation in the cells of A. tumefaciens, but the effect of Bfr deficiency on iron accumulation is severer than Dps deficiency and the double mutant ΔbdF has the least intracellular iron content. All three ferritin‐deficient mutants showed a decreased tolerance to 3 mM H2 O2 in comparison with the wild type. The tumour induced by each of three ferritin‐deficient mutants is less than that of the wild type. Complementation reversed the effects of ferritin deficiency on the growth, iron homeostasis, oxidative stress resistance, and tumorigenicity of A. tumefaciens . Therefore, ferritin plays an important role in the pathogenesis of A. tumefaciens through regulating iron homeostasis and oxidative stress survival. Abstract : Deficiency of two Agrobacterium tumefaciens ferritins, Bfr and Dps, not only affects the growth under iron stress, reduces the iron accumulation, and impairs the oxidative resistance, but also attenuates the virulence.